Thursday

March 5, 2015

March 5, 2015

Posted by **JOSHI** on Saturday, June 23, 2012 at 3:18am.

1) (4/3x+3/4y)^3

- maths -
**Reiny**, Saturday, June 23, 2012 at 8:50amin general

(a+b)^3 = a^3 + 3a^2 b + 3a b^2 + b^3

then ...

(4/3x+3/4y)^3

= (4/3)^3 x^3 + 3(4/3)^2 x^2 (3/4)y + 3(4/3)x (3/4)^2 y^2 + (3/4)^3 y^3

= 64x^3/27 + 144x^2 y/36 + 108xy^2/48 + 27y^3/64

= 64x^3/27 + 4x^2y + 9xy^2/4 + 27y^3/64

testing by letting x=1, y=1

(4/3 + 3/4)^3 = appr 9.0422..

my expression at the end = .0422..

I assume you meant it the way you typed it

if you meant

( 4/(3x) + 3/(4x) )^3 it would totally change the answer.

**Answer this Question**

**Related Questions**

maths - Q.1. write the expansions: (3x+4y)^3

maths - Find the expansions of (1-x)^6 and (1+2x)^6 as far as the terms in x^3. ...

Fibonacci numbers - I have been working on this question all day and can not ...

CALC - I am sorry i still dont know how to start. and i am sorry for the problem...

Math - The least upper bound of a set of real numbers in (0,1) whose decimal ...

Math - I need help trying to write out these binomial expansions: they all need ...

precalculus - Explain how the graph of f(x)=(-2)/(x-3)^2 can be obtained from ...

Pre-calculus - Explain how the graph of f(x)=(-2)/(x-3)^2 can be obtained from ...

Numerical Analysis - Use Taylor series expansions (zero through fourth order) to...

Maths - suppose function f,g,h and l are defined as follow:f(x)=4xsquared-5x+1,g...